Innowacyjność strategii jako czynnik sukcesu przedsiębiorstw - Kaleta, Andrzej (Strategy Innovation as an Enterprise Success Factor, 2006)
Current conditions of economic development favour unique companies which challenge stereotypes. Innovative and non-standard strategy is a condition of significant differentiation. National and international experience proves that novel strategies are key to success in business. Companies which avoid risk of taking up pioneering path of development are doomed to failure, at least in a long-term perspective.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 98-104